The Effectiveness of Listing Under the U.S. Endangered Species Act: An Econometric Analysis Using Matching Methods (2007)
Diametrically opposed views of the effectiveness of the United States Endangered Species Act (ESA) co-exist more than 30 years after the Act's creation. The evidence marshaled to date for and against the ESA suffers from a problem common in analyses of biodiversity protection measures: the absence of a well-chosen control group. We demonstrate how matching methods can be used to select such a control group and thereby estimate how species listed under the ESA would have fared had they not been listed. Our results show that listing a species under the ESA is, on average, detrimental to species recovery if not combined with substantial government funds. In contrast, listed species with such funding tend to improve. Our analysis offers not only new insights into a controversial debate, but also a methodology to guide conservation scientists in evaluating the effectiveness of society's responses to biodiversity loss